Primers for Detecting katG Gene Mutations in Isoniazid-Resistant Mycobacterium Tuberculosis - Widodo Widodo; Ahmad Riyadi; Daniel Joko Wahyono; Hendro Pramono; Sunarto Sunarto (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Pulmonary tuberculosis is a disease caused by Mycobacterium tuberculosis infection, which is a health problem in Indonesia. Exploration of the treatment point of anti-tuberculosis drug resistance genes is very important for determining the appropriate gene-target markers of resistance. This study aimed to analyze the role of the katG/Rv1908c gene in Mycobacterium tuberculosis as a marker of isoniazid resistance, and to use mutation analysis data to design specific primers for dominant isoniazid-resistance mutations. We conducted descriptive research using a cross-sectional sampling method. The samples in this study were 10 MDR-TB isolates collected at the Health Laboratory and Calibration Testing Center of Central Java Province (Balapkes and Pak Prov Jateng). The research procedure included denaturing target primer sequencing of Mycobacterium tuberculosis DNA, DNA extraction, and PCR procedures. PCR was performed using BIONEER Exceller 96 with Gotaq Green Master Mix Kit reagents. PCR results were sequenced using the Sanger method at PT. Genetika Science. The Sanger sequencing results were analyzed using the BioEdit program to align the sequences. The spliced Mycobacterium tuberculosis DNA was analyzed using MEGA 10 software to identify mutation sites for comparison with the wild-type H37Rv and to determine the katG gene mutation site within the mapped region. The results of the DNA sequencing analysis using the Sanger sequencing method obtained that the katG gene mutation was dominated by Ser315Thr (80%) which was a single mutation, a double mutation at Ser315Thr+Ala221Asp (10%), a double mutation at Ser315Thr+Arg249Cys (10%), and the results of Primer F > 5'-GATCACCAGCGGCATCGAG-3' Primer R > 5'-CTCTTCGTCAGCTCCCACTC-3' and Primer R >5'-GATCACCACCGGCATCGAG-3' were able to amplify the Ser315Thr gene target as a detection primer. The conclusion is that the dominant mutation conferring isoniazid resistance is Ser315Thr, and the primers used to target the mutation work well.